ALGORITMA DALAM PRAKTIK PENEMUAN HUKUM MODERN - Aritonang, Rasamala (Faculty of Law, Parahyangan Catholic University, 2024)
A defining characteristic of modern society is its reliance on general rules and regulations that derive legitimacy from scientific methods and findings, instead of customs or tradition. These rules are not typically enacted by individuals such as kings or priests with divine or prescriptive authority but are instead guided by rational and impersonal principles developed by